Montmorillonite- hydrothermal carbon nanocomposites: synthesis, characterization and evaluation of pesticides retention for potential treatment of agricultural wastewater - Zelaya Soulé, María Emilia (2020)
Montmorillonite (M) was modified by addition of hydrothermal carbon (HC) in order to obtain pesticideadsorbent materials. Carbohydrates were used as carbon source, and in some cases, also phosphoric acid wasapplied as activation agent. The M-HC hybrids maintain the negative electrical surface charge of their precursors(between -35 mV and -15 mV), while lower specific surface areas (around 6 m2 g-1) than that of M sample (66m2 g-1) were found. The loss of specific surface could be assigned to the carbon location on both the external andthe interlayer surface of the M sheets, as was confirmed by FTIR, zeta potential measurements and XRDanalysis. For M-HC products obtained by acid treatment, despite their structure alteration, the specific surfacevalues remained similar to that of M sample (around 70 m2 g-1).The M-HC products with or without acid treatment retain almost 100 % adsorption of chlorpyrifos (CPF) andthiabendazole (TBZ) as that obtained for M sample, under the tested conditions. Coagulation studies revealedthat M-HC products evaluated showed better precipitation property than that of M sample, which would precludethe typical montmorillonite gel formation that usually block filters and reactors.